Faculty of Education Students' Perceptions of Social Distance towards Different National Identities - Halil İbrahim Eyice; Fatih Yazıcı (Uluslararası Türk Eğitim Bilimleri Dergisi)
Simultaneous triangulation of mixed models was used in this study, which aimed to identify pre-service teachers' perceptions of social distance toward Armenians, Syrians, and Africans and the reasons for these perceptions. The survey model was used in the quantitative dimension of the study, and the case study design was used in the qualitative dimension. The study sample consisted of 357 preservice teachers from various programs and grade levels who were continuing their undergraduate education. The Social Distance Scale developed by Bogardus (1925) and an open-ended questionnaire were used to collect the data. Descriptive analysis was used to analyze qualitative data. As a result of the study, Syrians, followed by Armenians and Africans, were found to be the communities to which the pre-service teachers felt the most social distance. When the participants' justifications for the perceived social distance were analyzed, it was found that the perceived threat they felt from communities different from themselves was effective in creating social distance. The results of the study reveal that the scope and content of undergraduate teacher training programs should be revised in terms of respect for diversity.